The Impact of Covid-19 to Indonesian Education and Its Relation to the Philosophy of “Merdeka Belajar” - Azmil Abidah; Hasan Nuurul Hidaayatullaah; Roy Martin Simamora; Daliana Fehabutar; Lely Mutakinati; Nadi Suprapto (Studies in Philosophy of Science and Education, 2020)
The Covid-19 pandemic is now beginning to spread to the world of education. The Ministry of Education and Culture (MOEC) is currently based on official information, ready with all scenarios, including encouraging online learning for students. This article is a kind of position paper—it clearances one side of a debatable opinion about a hot issue. The aim of a position paper is to persuade the reader that our opinion is valid and defensible. In regards to our position as researchers, then, the point of view is separated into four parts: The philosophy of “Merdeka Belajar”, physical distancing, social distancing and self-quarantine, digital learning in Indonesia to face Covid-19, ‘Merdeka Belajar’, digital learning, Covid-19, and authors’ view.